Case-control studies in cancer patients as a surveillance system of occupational exposure in the European Community. European Community Working Party. Issue 4 (August 1993) - Rona, R J; Taub, N A; Rasmussen, S
Abstract : STUDY OBJECTIVE–The main aim was to detect known relationships between lung and blood cancers and various occupational exposures (using job titles as proxies) using a case-control design. The suitability of this system for routine surveillance could then be assessed. DESIGN–A case-control study was carried out in 1989. SETTING–Hospitals in eight European Community countries. SUBJECTS–Men aged 25 to 75 years with incident and prevalent cancer of the lung (190 cases), haematopoietic system (210 cases), or gastrointestinal tract (245 controls) were studied. MEASUREMENTS AND MAIN RESULTS–The crude estimate of the overall odds ratio exposure (OR) for relevant occupational exposure of lung cancer relative to gastrointestinal cancer was 1.20 (95% confidence interval (CI) 0.82, 1.77). In a logistic regression analysis adjusting for country, age at diagnosis, smoking, and alcohol consumption, the overall OR was not greatly changed. A significant interaction of occupational exposure and age at diagnosis showed that lung cancer patients diagnosed at a younger age had a higher OR than patients diagnosed at an older age. Thus, the overall, insignificant result may have been due to a low reliability of occupational history in older age or to a selective mechanism related to age. The overall OR for occupational exposure of cancer of the blood relative to gastrointestinal cancer was 0.88 (95% CI 0.60, 1.31). The logistic regression analysis did not alter these results. CONCLUSION–A surveillance based on a case-control design using job titles would not be sensitive enough to detect possible occupational risks.